Cardiac impact of hypoglycaemia (2017)
Acute or chronic hypoglycaemia, induced by insulin or other oral antidiabetic drugs in a therapeutic context, constitutes a cardiovascular risk factor. It leads to endothelial dysfunction and atherogenesis through pro-inflammatory mechanisms, as much as or more important than hyperglycaemia, with the aggravating factor of inducing arrhythmogenic and ischaemic sudden death. Conclusion Hypoglycaemia is a real threat for the myocardium, not only due to its immediate pro-arrhythmic effects, that may be associated with sudden death syndrome, but also due to the pro-inflammatory and atherogenic effects. These are all significant risk factors for the development of cardiovascular disease, making it desirable, and clinically relevant to prevent hypoglycaemic episodes of any intensity and duration in any type of diabetic patient. This is particularly important in those that have a pathological myocardial substrate that can lead to an increase in the risk of sudden death: compromised systole function, ventricular arrhythmias, atrial fibrillation, coronary disease, hypertrophic cardiomyopathy, arrhythmogenic genotype, and a history of resuscitation. © 2017 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular